Estrous Cycle and Gestational Age-Dependent Expression of Members of the Interleukin-36 Subfamily in a Semi-Allogeneic Model of Infected and Non-Infected Murine Pregnancy - Murrieta-Coxca, José Martin; Gómez-Chávez, Fernando; Baeza-Martínez, Damariz Adriana; Cancino-Diaz, Mario Eugenio; Cancino-Diaz, Juan Carlos; Pérez-Tapia, Sonia Mayra; Reyes-Maldonado, Elba; Rodríguez-Martínez, Sandra (Frontiers in Immunology, 2016)
The IL-36 subfamily is a recently described group of cytokines with pro-inflammatory behavior, comprising three agonists (α, β and γ), its receptor (R) and one antagonist (Ra). The expression and function of IL-36 subfamily members in the estrous cycle in healthy and infected pregnancy have not been described. We evaluated mRNA and protein expression of IL-36 family members during the estrous cycle, implantation, fetal development and post-labor periods in a model of allogenic pregnancy in mice. We also explored the ability of Listeria monocytogenes to modulate expression of IL-36 subfamily members during pregnancy. Expression of IL-36 subfamily members showed different expression during the estrous cycle and pregnancy, but was induced at estrous, 16.5 days post coitum (dpc), 18.5 dpc and labor. IL-36 subfamily members showed a characteristic distribution in the glandular epithelium, perimetrium, myometrium, and stratum vasculare. Infection with Listeria monocytogenes during pregnancy induced strong production of IL-36 subfamily members, an observation that correlated with an increasing prevalence of fetal loss. Conclusions: IL-36 agonists showed specific patterns of mRNA and protein expression that might suggest functional specialization or specific target cells. Infection with Listeria monocytogenes during pregnancy induced strong production of IL-36 subfamily members.